Vulvar basal cell carcinoma: report of a case involving the mucosa and review of the literature - Marie Caucanas; Gebhard Müller; Olivier Vanhooteghemv (PAGEPress Publications, 2011)
We report the case of woman who presented a vulvar basal cell carcinoma (BCC) on the inner part of the labium majus, treated with local resection. Vulvar BCC is a rare cancer but can be long misdiagnosed due to a non-specific presentation. Though even rarer, BCC involving the mucosal side of the labium majus has to be considered in the differential diagnosis of the vulvar tumors. A complete excision with free margins is the treatment most recommended. Other recommendations include the early identification of aggressive subtypes, which carry a greater risk of recurrence and spreading potential as well as a long-term follow-up with exhaustive muco-cutaneous examination.